Penatalaksanaan Fisioterapi pada Kasus Frozen Shoulder Et Causa Capsulitis Adhesiva dengan Modalitas MWD, TENS, dan Terapi Latihan di RS PUSDIKKES PUSKESAD - Ika Rahman; Yuniat Irawati; Lona Thesalonika (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Frozen Shoulder caused by Adhesive Capsulitis is a musculoskeletal disorder of the glenohumeral joint characterized by pain, restricted range of motion, and decreased functional ability due to inflammation and fibrosis of the joint capsule. This condition commonly affects individuals aged 40–65 years and significantly interferes with daily activities if left untreated. This case study aimed to evaluate the effectiveness of Microwave Diathermy (MWD), Transcutaneous Electrical Nerve Stimulation (TENS), and Exercise Therapy in reducing pain, improving shoulder range of motion, increasing muscle strength, and restoring functional activities in a patient with Frozen Shoulder. A quantitative descriptive case study was conducted on one patient with left Frozen Shoulder at RS Pusdikkes Puskesad. Clinical outcomes were evaluated over eight treatment sessions using the Visual Analog Scale (VAS), goniometer, Manual Muscle Testing (MMT), and Shoulder Pain and Disability Index (SPADI). The results demonstrated reductions in resting pain from 2 to 0, tenderness from 4 to 0, and movement pain from 6 to 0. Shoulder range of motion improved from flexion 90° to 180°, extension 40° to 60°, abduction 90° to 180°, internal rotation 45° to 90°, and external rotation 30° to 90°. Muscle strength increased from grade 4 to grade 5, while the SPADI score decreased from 37.5 to 1.5, indicating marked functional recovery. It can be concluded that the combination of Microwave Diathermy (MWD), Transcutaneous Electrical Nerve Stimulation (TENS), and Exercise Therapy is effective in reducing pain, improving shoulder mobility, increasing muscle strength, and restoring functional ability in patients with Frozen Shoulder caused by Adhesive Capsulitis.